2016
DOI: 10.1136/postgradmedj-2016-134362
|View full text |Cite
|
Sign up to set email alerts
|

The work environment of junior doctors: their perspectives and coping strategies

Abstract: Psychologically distressed junior doctors need recognition, support and treatment. Future interventions should focus on improving work environment, job satisfaction, provision of supports, use of healthy coping strategies and improving work-related relationships. This could potentially reduce levels of psychological distress in junior doctors, optimise delivery of healthcare to patients and maximise workforce potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 25 publications
(24 reference statements)
0
29
0
Order By: Relevance
“…Across the 48 studies, a pooled cohort of 36 266 participants was formed. 4 , 10 , 11 , 12 , 13 , 17 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 The median number of recruited trainee physicians was 203 (range, 58-16 394). One study 43 did not specify participants’ sex; of the total cohort, 18 781 participants (52%) were men and 17 315 participants (48%) were women; median age was 29 years (range, 24.6-35.7).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Across the 48 studies, a pooled cohort of 36 266 participants was formed. 4 , 10 , 11 , 12 , 13 , 17 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 The median number of recruited trainee physicians was 203 (range, 58-16 394). One study 43 did not specify participants’ sex; of the total cohort, 18 781 participants (52%) were men and 17 315 participants (48%) were women; median age was 29 years (range, 24.6-35.7).…”
Section: Resultsmentioning
confidence: 99%
“…The median response rate for cross-sectional studies was 61% (range, 15%-90%). Twenty-four studies 31 , 33 , 34 , 35 , 37 , 41 , 42 , 43 , 46 , 47 , 48 , 49 , 52 , 53 , 57 , 58 , 60 , 61 , 64 , 65 , 66 , 67 , 68 , 70 (50%) had an adapted NOS score greater than or equal to 6 (range, 2-8). Eleven factors were identified in this review ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…45 Another study from Australia in 2016 reported the mean K-10 score as 17.2±6.3 among junior doctors and attributed their findings to high working hours and increased responsibilities. 46 Medical students are a favourite group for insomnia researchers and many studies have been conducted to assess the level of insomnia and its stressors. A study from Iran in 2014 reported the mean score of the ISI as 9.79±5.03 among medical students.…”
Section: Discussionmentioning
confidence: 99%
“…Doctors in training appear to be particularly susceptible. In recent Australian surveys, one in five medical students reported suicidal ideation in the preceding 12 months, while 50% of junior doctors experience moderate to high levels of distress 3 , 4 …”
Section: The Scope Of the Problemmentioning
confidence: 99%
“…Collegiality is at risk of extinction — perhaps a consequence of reduced working hours and increasing home demands in an older, expanding junior doctor workforce, who are now experiencing unhealthy high levels of peer competition. In addition, one‐third of junior doctors have experienced workplace bullying, particularly affecting women 4 . As gruelling as I recall basic physician training, there was never a sense of anxiety among my peers about future job opportunities in our chosen specialties.…”
Section: Factors Contributing To Suicide Riskmentioning
confidence: 99%